Sistema De Inteligencia De Negocios Para Los Procesos De Instalación Y Mantenimiento De Redes Adsl Y Tv De La Empresa Servicios Y Comunicaciones Armenia Quindío (2016)
The company SYCSA was devoted to administration of operational processes of network installation and maintenance of internet, telephony and television. Currently provides its services to the company Movistar, this must comply with operational policies such as, minimize the response time in the requests of the clients, increase productivity, reduce the repeatability in the failures reported by users. Currently, the processing of the information and the monitoring of compliance of these parameters are carried out independently by each one of the engineers analysts of the respective, which record their data in Excel worksheets, which means that the information is not centralized, hindering the diagnosis and monitoring of the performance of the different work teams and the productivity of the company. The work of grade "Business Intelligence System for the installation and maintenance of ADSL networks and TV of the company services and communications Armenia Quindío", aims to design a model of business intelligence to support the processes of the company, in order to obtain clear and detailed information of the movements of each one of the processes and in this way make smarter decisions and productive.